Reinforcement of human resources in implementing healthy indonesian program with family approach - Retno Widiarini; Djazuly Chalidyanto; Eva Rusdianah (Journal of Public Health Research, 2020)
Background: The Healthy Indonesia Program is a government program implemented with the Family Approach (HIP-FA) through a survey on healthy families. However, the quality of the program depend on the performance of the Human Resources (HR). This study aims to examine various aspects of HR in implementing the program at health centers. Design and methods: Data were collected through in-depth interviews, Focus Group Discussions, and document review on eight informants at the Health Office center. Results: Four themes revealed from the study: being burdened, feeling overwhelmed, feeling incompetent, and confused managing technology. The results showed that the implementation of the HIP-FA survey is an additional burden for health center staff. Conclusions: It is necessary to strengthen the implementation of all programs through continuous training and education, positive affirmation, recalculating employee workload and remunerations.